Fact checking during COVID-19: a comparative analysis of the verification of false contents in Spain and Italy - Peña Ascacíbar, Gonzalo (2021)
With the spread of COVID-19 around the world, a large number of hoaxes or false and out of context news are also spreading. In the moment, the studies that have been carried out regarding the topic have mainly focused on single-territory research. For this reason, we consider it pertinent to widen the spectrum and observe the behaviour of more than just one country. More specifically, the present study compiles a comparative analysis between Spain and Italy regarding fake contents and the diverse elements that have come into play in the media during the first months of the new type of coronavirus in Europe. To do this, we have used the fact checking platforms Maldita.es and Open. Once the information was collected, we created our own database systematizing the following five elements: type, broadcasting platform, format, general topic, and discursive axis. With the objective of having an adequate sample, we have selected a period beginning with the emergence of the first cases at the end of January until the end of May 2020. The research carried out over these five months has allowed us to develop a study with which to quantitatively and qualitatively verify how the discursive characteristics of false contents related to the pandemic have developed in different ways and times in each of the territories, while also sharing a series of similar topics between both.